In the air tonight - 525094 Tyler, Stephanie (Kuala Lumpur : MPH, 2011)
Former Delta Force operative Mace Stevens, who now runs a small bar, finds the memories of a mission he barely survived rushing back when Paige Grayson arrives, demanding answers about her stepbrother's death under his command.